Integration model in auto takaful insurance - Puspa Liza, Ghazali; Mustafa, Mamat; Puspita Puspa Sari, Abdul Ghani (Pushpa Publishing House, 2015)
Based on the statistic in year 2007, the fatal injury is 13.6% and increased to 15.5% in year 2009. Almost the road traffic injuries have not been protecting with motor PA coverage. This shows the road user still did not aware the important of motor PA policy takaful insurance. From here, the problem arises, the normal motor insurance policy did not cover the passenger in the vehicle especially the family member in the vehicle while was travelling. Many consumers in Malaysia are not included the personal assurance because of its separated package in auto takaful insurance. Even though, they strongly believe that an accident is always hunting their life at any angle. Therefore, the new proposed amendment in the auto takaful insurance must have integrated package plan in price and also riders. In this research, the writer introduces the integration model in auto takaful insurance for better consumer package.